Fluoxetine does not influence response to continuous theta burst stimulation in human motor cortex - Duncan K. Austin; Lourenço M. D. Amador; Lucia M. Li; Simon J. Little; John C. Rothwell (Neuropsychopharmacology Reports)
Abstract Aim Selective serotonin reuptake inhibitors are thought to exert a clinical effect through various mechanisms, including through alteration in synaptic plasticity. Repetitive transcranial magnetic stimulation can induce temporary changes in synaptic excitability in cerebral cortex that resemble long‐term potentiation and long‐term depression that serve as a measure of synaptic plasticity in vivo. A version of repetitive transcranial magnetic stimulation called continuous theta burst stimulation can induce inhibition of cortical excitability that can be measured through a motor evoked potential. Previous work has suggested that this response can be modulated by administration of selective serotonin reuptake inhibitors. Method Thirty‐one healthy volunteers received both fluoxetine 20 mg and placebo in randomly ordered sessions, followed by spaced continuous theta burst stimulation to motor cortex. Changes in Motor Evoked Potentials were then recorded over 60 min. Results The response to spaced continuous theta burst stimulation did not differ significantly between fluoxetine and placebo sessions. Spaced continuous theta burst stimulation produced a paradoxical excitatory response in an unexpected number of participants. Conclusion A single dose of fluoxetine 20 mg does not influence the response to continuous theta burst stimulation. Previous results suggesting an effect of selective serotonin reuptake inhibitors on inhibitory non‐invasive brain stimulation protocols may be due to insufficiently large sample sizes.